Safety of aggressive nutrition bundle-aggressive parenteral nutrition, standardized feeding policy, human milk fortification and probiotics in babies born less than 34 weeks of gestation: a prospective analytical cohort study - Shah, Mubashir H.; Rachwani, Nitin P.; Roshan, Reashma; Patwardhan, Gaurav; Parikh, Tushar; Kadam, Sandeep S. (International Journal of Contemporary Pediatrics, 2019)
Background: Despite changes in nutritional interventions in neonatal intensive care units worldwide, significant proportion of preterm babies are growth restricted at discharge. Authors intended to look at the feasibility of aggressive nutrition bundle (aggressive parenteral nutrition, standardized feeding policy, fortification and probiotics) in preterm neonates. Methods: This single centre prospective analytical cohort study, involving babies born before 34 weeks of gestation, was conducted in a tertiary hospital. Aggressive parenteral nutrition and enteral nutrition bundle intervention was started within 24 hours of birth. Clinical, laboratory and anthropometrical parameters were monitored longitudinally to ensure safety of this intervention. Results: Mean gestational age and birth weight of the cohort (n=107) was 30.6 weeks (SD±2.6) and 1147 grams (SD±287) respectively. Out of 107 babies, 67.3% (n=72) have extra uterine growth retardation (EUGR) at discharge and was more in small for gestational age neonates (p=0.001). With this aggressive parenteral and enteral nutrition bundle intervention, medical necrotizing enterocolitis (NEC) developed in 7.4 % (n=8) babies while surgical NEC was seen in 1.9%. (n=2). Early onset and late-onset sepsis occurred in 1.8% and 5.4% of babies respectively while mild hyperammonemia, mild hypertriglyceridemia, raised creatinine and urea developed in 12.4%, 4.6%, 7.4% and 11.7% respectively. Hyperglycemia and hypoglycemia were present in 8.8% and 5.6% babies respectively. Conclusions: Aggressive nutrition bundle (aggressive parenteral nutrition, standardized feeding policy, fortification and probiotics) can be safely employed in preterm babies. There is an urgent need to design a study to see the impact of this approach on incidence of EUGR in preterm babies.